Catalyzed and uncatalyzed procedures for the syntheses of isomeric covalent multi-indolyl hetero non-metallides: an account - Talukdar, Ranadeep (Beilstein Journal of Organic Chemistry, 2021)
Two or more indole molecules tailored to a single non-metal central atom, through any of their C2–7 positions are not only structurally engaging but also constitute a class of important pharmacophores. Although the body of such multi-indolyl non-metallide molecules are largely shared to the anticancer agent bis(indolyl)methane, other heteroatomic analogs also possess similar medicinal properties. This concise review will discuss various catalytic and uncatalytic synthetic strategies adopted for the synthesis of the non-ionic (non-metallic) versions of these important molecules till date.
Keywords: bisindole; heteroatom; indole; selenide; sulfide